PENGARUH KARAKTERISTIK PEGAWAI DAN MOTIVASI TERHADAP KINERJA PADA PEGAWAI KANTOR CAMAT TANAH KAMPUNG - Eka Septiani (Jurnal Ekonomi Sakti, 2021)
The aim of this research was to determine how much influence application employee behaviour and motivation in the office of Tanah Kampung regency with performance of employee.This research used quantitative method since researcher wanted to determine the measurement of X and Y variable. Population in this study is 20 people. Sampling technique used is a full sampling as many as 20 people. Data analysis techniques in this study ismultiple regresion analysis and coefficient of determination analysis.Questionaires were used as a tool in data collection method. The findings show that all hypothesis were proved to be significant employee behaviour and motivationhave a positive and significantinfluence with performance of employee. The implies that played as important roleemployee behaviour and motivation(individualy or simultaneously) in developing performance of employee.